Use of Autoplasma in the Prevention of Venous Thromboses during Endoprosthetic Replacement of the Hip Joint - S. A. Kravtsov; S. V. Vlasov; O. V. Shakurin; I. V. Vlasova (Общая реаниматология)
Hip joint endoprosthetic replacement (HJER) leads to hemodynamic disorders and massive intraoperative hemorrhage and presents a high risk (30—55% of cases) for postoperative deep vein thrombosis in the lower extremity, at the same time the possibility (12—22%) of massive pulmonary thromboembolism (PTE) is ruled out. So the choice of infusion-transfusion therapy is of paramount importance in these patients. The authors studied the efficiency of normovolemic hemodilution with the autoplasma (patented in the Russian Federation) in treating massive perioperative hemorrhage in patients undergoing HJER and in reducing postoperative thrombotic events. It was compared with infusion therapy comprising hydroxyethyl starch (130/0.4). All the patients had spinal anesthesia and standard postoperative analgesia in an intensive care unit. The administration of autologous fresh frozen plasma resulted in a 15% reduction in intraoperative blood loss, by increasing the coagulation potential and platelet aggregability. Postoperatively, there was an overall increase in the hypercoagulation potential, both the plasma link and platelet aggregability, in both groups. The use of autologous plasma by elevating the concentration of natural anticoagulants (AT III) by 9% could prevent 35 and 75% rises in soluble fibrin monomer complexes and D-dimer. In two patients from the comparative group, the postoperative period was complicated by the development of occlusive thrombosis of the femoral vein. Key words: intraoperative hemodilution, auto-plasma, vein thromboses.